Bentley, Old World Encounters - Cross-Cultural Conflicts And Exchanges In Pre-Modern Times - Lowry, Bullitt (Teaching History: A Journal of Methods, 1994)
In the last generation or so, any number of new approaches to the study of history-from Cliometrics to gender-have shown promise of new visions and new understanding. One of the richest of these new approaches is world history, dating in its modern incarnation to the 1960s. Today, the efforts of world historians are focused in the World History Association, with its newsletter and journal. Jerry Bentley, the author of Old World Encounters, is editor of that WHA journal, the Journal of World History. He is in the forefront of this new intellectual pursuit, in which a host of world historians are trying to put aside the distorting lens of traditional Eurocentrism (or even traditional Sinocentrism) and replace it with a truly global understanding.